(untitled) (Journal of Educational Sciences, 2023)
Following questions was affected in this article – types of mathematical problems, role and meaning of solving problems in men’s life (pupil, student), difficulties in solving mathematical problems, classification of mathematical problems due to the way of solving key. Tasks of arithmetics are various according to the contents and on difficulty of the decision. At the solution of some tasks doesn’t meet difficulties in a choice of this or that action. The choice of arithmetic actions and at the solution of many tasks is carried out on the basis of the communications existing between these sizes. Solution of each task purely arithmetic actions and logical conclusions, but not to the same extent: in one tasks arithmetic actions prevail, and reasonings and logical conclusions play so prevailing role others, after the logical conclusions the solution of a task is consolidated to thought tension. If the necessary data on arithmetics are acquired and problems of detailed type are already sorted, other problems of this sort are solved without effort. The article presents the results of a survey of teachers on the methodology of teaching mathematics and solving problems by schoolchildren. Key words: quantily , problem, teaching the methods of problem solving , types of arithmetical problems , ways of problem solving.